STRATEGI PENGEMBANGAN SEKTOR PERTANIAN SUB SEKTOR TANAMAN PANGAN DALAM UPAYA PENINGKATAN PDRB KABUPATEN PATI - Arif Syaifudin (Economics Development Analysis Journal, 2014)
Basically it is planning an effort to anticipate imbalances that occur in an initial balance. One of the roles of planning is as a reference for the development process to walk towards the goals to be achieved. The issues examined in this thesis are (1) a commodity food crops that have a competitive advantage and comparative in Pati, (2) how the planning development of food crops sub sector based on the completeness of the infrastructure that is owned in Pati. The subject in this study is a commodity food crops in pati. Methods of data collection include documentation a. Data analysis methods include (1) the Location Quotient (LQ), (2) Shift-Share Marquillas Esteban, (3) Typology Klassen, Skalogram (4), (5) Overlay.Based on the research known the development of commodities rice sub-district sukolilo sub-district, are located in sub-district kayen, sub-district starch, a cork, sub-district and sub-district margorejo. Commodities of a corn plant sub-district sukolilo and sub-district kayen. Commodities tanamn soybean kayen sub-district, sub-district starch, and sub-district cork. Commodities of pea plant land sub-district margorejo and sub-district gembong. Commodities of green bean plant sub-district starch, a cork, sub-district and sub-district margorejo. Commodities plant of the manioc sub-district gembong and sub-district margoyoso. Commodities sub-district winong, plant of the sweet potato sub-district pucakwangi, sub-district jaken, sub-district jakenan, and sub-district wedarijaksa.